Meningkatkan Aktivitas dan Hasil Belajar IPS Melalui Model Pembelajaran Kooperatif Tipe Snowball Throwing Siswa Kelas 6 SDN 3 Jatibateng - Yatinah, Yatinah (Universitas Nusantara PGRI Kediri, 2023)
Based on interviews and observations from both class teachers and students, the learning process at SDN 3 Jatibanteng, Jatibanteng District, teachers still use a lot of methods which are dominated by the lecture method which makes the teacher the center of teaching and learning activities or teacher centered. The purposes of this study are 1) To find out the increase in social studies learning activities for 6th grade students at SDN 3 Jatibanteng in 2021-2022 after applying the Snowball Throwing cooperative learning model. 2) To find out the increase in social studies learning outcomes for 6th grade students at SDN 3 Jatibanteng in 2021-2022 after applying the Snowball Throwing type cooperative learning model. This study used two rounds of action research. Each round consists of four stages: design, activity and observation, reflection and revision. The target of this research is 6th grade students at SDN 3 Jatibanteng, Jatibanteng District, in 2021/2022. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis it was found that the activity and student learning outcomes increased from cycle I to cycle II. The conclusion from this study is that the Snowball Throwing type cooperative learning model has a positive effect on the activities and learning outcomes of grade 6 students at SDN 3 Jatibanteng, Jatibanteng District in 2021-2022, and this learning can be used as an alternative to social studies learning.